Dampak Perkembangan Pariwisata Terhadap Kondisi Sosial-Ekonomi Masyarakat Di Desa Wisata Coal, Kabupaten Manggarai Barat - Sukur, Maria Paulista S.; Sanjiwani, Putri Kusuma (JURNAL DESTINASI PARIWISATA; Vol 11 No 1 (2023): VOL 11, NO 1 (2023): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2023)
Coal Village is geographically located at the eastern end of West Manggarai Regency. The purpose of this study was to determine the impact of tourism on the socio-economic conditions of the local community in Coal Village. The research method used is qualitative the types of data in this study are qualitative and quantitative data and the data sources used are primary data and secondary data with the technique of determining the informant used is a purposive sampling technique. Techniques of data analysis using qualitative descriptive analysis. The results of the study found that the development of tourism had a positive impact on the socio-economic life of the community such as new job opportunities, an increase in income, and investment in education, but the impact of tourism activities was only felt by some of the people who involved in tourism activities in Coal Village. Keywords: Impact, Tourism, Socio-Economic, Local People, and Coal Village